Analisis Penerapan SAK-EMKM pada Laporan Keuangan UMKM : Studi Kasus Kedai Sayur Ibu Diana - Salsa Oktavia Salbina; Indri Jihani; Naifah Amelia Ramadhani; Lutfatul Umamah; Abdul Qodar Riyanto (Universitas 45 Surabaya, 2026)
MSMEs play an important role in the economy, even though most business actors still find it difficult to prepare financial statements in accordance with accounting standards. This is also the case with Ibu Diana's Vegetable Stall MSME, which still uses simple record keeping, thereby reducing the quality of the financial information produced. Based on this, this study aims to analyze the implementation of the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK-EMKM) at Ibu Diana's Vegetable Shop and identify the benefits and obstacles encountered in implementing these standards. This study uses a qualitative method with a case study approach. Informants were determined purposively, namely the owner of Kedai Sayur Ibu Diana, then expanded through the snowball technique to obtain additional sources. Data were collected through triangulation techniques, which included in-depth interviews about how to record business activities and documents related to finance. The results of the study show that Kedai Sayur Ibu Diana has not fully implemented SAK-EMKM due to limited understanding, lack of transaction evidence, and the absence of an organized recording system. However, the implementation of standards has the potential to provide benefits in the form of increased recording accuracy, reliability of financial information, and ease of decision making. This study shows that accounting assistance and training are very important for MSME players so that they can effectively implement SAK-EMKM.